Varicella Pneumonia Complicating Pregnancy: A Report of Seven Cases - Teresa J. Schutte; Louise C. Rogers; Pleas R. Copas (Hindawi Limited, 1996)
Background: Pneumonia is the most common complication of varicella-zoster infection in adults and has potentially devastating effects when complicating pregnancy. Due to the significant morbidity and mortality associated with this complication during pregnancy and the small number of reported cases in the literature, we present this report to help educate physicians who care for pregnant women.